IDENTIFY MAIN FACTORS THAT INFLUENCE CORRUPTION AND SUGGEST HOW TO ERADICATE THE CORRUPTION PROBLEM IN INDONESIA - Subagio subagio (Association of Certified Fraud Examiners Indonesia Chapter, 2016)
Ccorruption is an extra ordinary crime which has complex problem. There are many causes of corruption; and ccorruption has negative impact to many sectors, which is causing huge losses to the state and society. During the last decade, since the Corruption Eradication Commission (CEC) of the Republic of Indonesia has been established, the eradication of corruption cases has been done massively. However, the amount of corruption cases which have been handled by law enforcement agencies tend to increase by year to year. This paper will identify what factors are causing corruption and provide the ideas how to eradicate the corruption in Indonesia. There are at least five factors that cause corruption in Indonesia. The first one is politic factor. Secondly, is ineffective of system. The third is incentive or financial pressure factor. The fourth is due to the weak of law enforcement. The last of corruption causes is lack of integrity. This paper also provides the problem solving of corruption which is a latent endemic problem in Indonesia based on law number 30 of 2002 and identify the main causes of corruption. By identifying the root causes of corruption, hopefully it can be expected for eradicating corruption effectively and efficiently.